2018
DOI: 10.1111/jar.12537
|View full text |Cite
|
Sign up to set email alerts
|

Health problems of people with intellectual disabilities in Dutch out‐of‐hours primary care

Abstract: Background Little is known about the health needs of people with intellectual disabilities who access out‐of‐hours primary care services, raising concerns about accessibility and quality of care for this group. This study aims to identify commonly presented health problems of people with intellectual disabilities in this specific setting compared with the general population. Method Cross‐sectional study with routine data at two out‐of‐hours cooperatives with a total of 41,166 persons aged 20–65 requesting outo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The situations and health needs of people with ID are often very complex. People with ID are at risk for a number of health problems (Heutmekers et al, 2018). Identifying the problems can be challenging.…”
Section: Introductionmentioning
confidence: 99%
“…The situations and health needs of people with ID are often very complex. People with ID are at risk for a number of health problems (Heutmekers et al, 2018). Identifying the problems can be challenging.…”
Section: Introductionmentioning
confidence: 99%
“…In accordance with previous research (Pouls et al, 2021), our review highlighted significant gaps in knowledge among GPs regarding mental health conditions in people with learning disabilities. This may partially explain the findings of one study that mental health conditions were not among the most common health problems identified among people with learning disabilities in primary care (despite high prevalence), with the authors suggesting there may be diagnostic over‐shadowing from physical health conditions (Heutmekers et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Published guidance for the care of adults with learning disabilities in primary care includes advice for assessing mental health, behavioural conditions and pharmacology (Sullivan et al, 2018). However, despite guidance and high prevalence of mental health conditions among people with learning disabilities, none were identified among ten most commonly presenting conditions to Dutch out‐of‐hours primary care services for people with learning disabilities, and the authors suggest this may be due to diagnostic over‐shadowing by physical health conditions (Heutmekers et al, 2019). Further, the second most frequent reason for emergency department visits by people with learning disabilities in Canada related to mental health conditions and behavioural disorders (Durbin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation